2019
DOI: 10.1002/tcr.201981201
|View full text |Cite
|
Sign up to set email alerts
|

Cover Picture: Development of Chemical Probes for Functional Analysis of Anticancer Saponin OSW‐1 (Chem. Rec. 12/2019)

Abstract: This cover picture shows that an anticancer saponin OSW‐1 from Ornithogalum saundersiae was derivatized through site‐selective modification to provide a set of chemical probes for biological analysis. See the Personal Account by Rina Komatsu and Kaori Sakurai (DOI: 10.1002/tcr.201900042).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Cations with azulene moieties, which are non-benzenoid aromatics, have been reported for a long time. [78][79][80][81][82] Ito et al reported the redox behavior of several derivatives with multiple azulene skeletons, and their electrochemical properties have been investigated in detail. [83,84] Upon one-electron oxidation of a seven-membered ring, a nonbenzenoid tropylium cation, which acquires Hückel aromaticity, is generated.…”
Section: Azulene-embedded Highly Strained Hydrocarbonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cations with azulene moieties, which are non-benzenoid aromatics, have been reported for a long time. [78][79][80][81][82] Ito et al reported the redox behavior of several derivatives with multiple azulene skeletons, and their electrochemical properties have been investigated in detail. [83,84] Upon one-electron oxidation of a seven-membered ring, a nonbenzenoid tropylium cation, which acquires Hückel aromaticity, is generated.…”
Section: Azulene-embedded Highly Strained Hydrocarbonsmentioning
confidence: 99%
“…Azulene is a molecule of historical interest because of its abnormal photophysical properties; [76,77] it exhibits a deep blue color due to its narrow HOMO–LUMO energy gap and anti‐Kasha fluorescence from S 2 to S 0 . Cations with azulene moieties, which are non‐benzenoid aromatics, have been reported for a long time [78–82] . Ito et al.…”
Section: Closed‐shell Neutral Donorsmentioning
confidence: 99%
“…The tropylium cation (C 7 H 7 + ; A ; Figure 1A), first discovered in 1891, [1,2] stands as a cyclic, planar molecule endowed with 6π electrons and a positive charge delocalized over the entire 7‐membered ring. According to the Hückel rule, this species is classified as aromatic and displays notable stability, as demonstrated by the isolation of stable tropylium compounds [3–7] . Despite their aromaticity, tropylium cations exhibit electrophilic reactivity as Lewis acids and oxidants, which has led to their utilization as catalysts and stoichiometric reagents in a diverse array of organic transformations [8,9] and as functional organic dyes/chromophores in material sciences [10–17] …”
Section: Figurementioning
confidence: 99%